Profile of morphological characters among male and female buffalo (Bubalus bubalis) populations in Kaliakah Village, Bali Province, Indonesia - Almaududy, Khairul U.; Nurmawati, Ira; Basith, Abdul (Syiah Kuala University, 2023)
Buffaloes (Bubalus bubalis) in Kaliakah Village are exploited in the makepung lampit tradition, in addition to food and agricultural tools. However, the population of buffaloes in Kaliakah Village is very small hence information on their morphology is needed to inform conservation efforts. This study aimed to describe qualitative and quantitative characters in the morphology of male and female buffaloes in Kaliakah Village. This survey study was analyzed on 24 male buffaloes and 30 female buffaloes. Qualitative characters observed consist of body shape, body color, eye color, and horn shape, while quantitative characters measured consist of chest girth (CG), leg length (LL), body length (BL), head length (HL), neck length (NL), tail length (TL), and estimated body weight (BW). The study results revealed variations in body shape (stocky and fat), body color (black and albino), and eye color (black and reddish black) in both male and female buffaloes. Male buffaloes have a CG of 167 19.18 cm, LL of 57.63 5.23 cm, BL of 128.13 7.60 cm, HL of 31.38 3.50 cm, NL of 49.25 5.99 cm, TL of 61.88 6.53 cm, and BW of 740.79 198.59 kg. Female buffaloes had a CG of 160.40 16.53 cm, LL of 57.17 4.31 cm, BL of 127.39 7.55 cm, HL of 30.72 3.67 cm, NL of 72 5.46 cm, TL of 60.56 6.48 cm, and BW of 700.94 168.87 kg. Based on ANOVA (one-way) analysis, there was no significant differences between the quantitative characters of male and female buffaloes. Based on an analysis of correlation, there are differences in quantitative characters that are strongly correlated among male and female buffaloes.